Serum neopterin levels in women with preeclampsia: a systematic review - Vasilios Pergialiotis; Nikoleta Karampetsou; Panagiotis Zoumpourlis; Nikolaos Papantoniou; Nikolaos Thomakos; Georgios Daskalakis (Taylor & Francis Group, 2018)
Objective: Neopterin is a pteridine that is produced following activation of human macrophages upon stimulation with the cytokine interferon-gamma. Several studies suggest its association with preeclampsia and the purpose of the present study is to evaluate this assumption. Methods: We searched the Medline (1992-2018), Scopus (1993-2018) and Google Scholar (1993-2018) databases. All articles that evaluated serum neopterin levels in patients with preeclampsia were held eligible for inclusion, regardless of the trimester of pregnancy in which the measurement was performed. Case reports, animal studies and previous reviews were excluded. Results: A total of 10 studies were finally included in the present review, with a total number of 3,529 pregnant women. Among them 446 were diagnosed with preeclampsia. The majority of included studies reported that serum neopterin was significantly higher in patients with preeclampsia, compared to normotensive pregnant women (p < .05). One study reported that serum levels seem to correlate with the severity of the disease; as patients with HELLP had significantly higher values of neopterin compared to patients with mild and severe preeclampsia. None of the included studies proposed a cut-off value that would help assess the predictive accuracy of this protein for the detection of preeclampsia. Conclusion: Although current data seem to be promising, neopterin remains far from being used in current clinical practice as a biomarker that would help predict and follow-up patients that develop preeclampsia. Future studies are needed, to determine the optimal timing for its measurement and to propose potential cut-off values that would help in this direction.